The pragmatic maxim essays on Peirce and pragmatism - Hookway, Christopher (Oxford : Oxford University Press, 2013)
Christopher Hookway presents a series of essays on the work of Charles Sanders Peirce, the 'founder of Pragmatism' and one of the most important and original American philosophers. He illuminates how Peirce's writings on truth, science, and the nature of meaning contribute to philosophical understanding in ongoing debates.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on Nov. 13, 2012).
Keywords: Peirce, Charles S. -- 1839-1914.; Pragmatism